Protective and risk physical activities for adolescent idiopathic scoliosis: a systematic review identifying one-hour daily activity threshold and Chinese school-based prevention framework - Guan, Yujie; Zhao, Bin; Fan, Yongchun; Li, Yunchao; Wang, Haozhe (Frontiers in Sports and Active Living, 2025)
ObjectiveTo systematically review the association between different types and intensities of physical activity and adolescent idiopathic scoliosis (AIS) risk, synthesize evidence on dose-response relationships between physical activity and AIS prevention, and propose school intervention recommendations.MethodsLiterature related to physical activity for preventing scoliosis and promoting spinal health in adolescents was retrieved from PubMed, Cochrane Library, Web of Science, Scopus, China National Knowledge Infrastructure, and Google Scholar, published between January 2015 and January 2025. After screening, key information was extracted, and methodological quality was assessed using the Newcastle-Ottawa Scale for case-control and cohort studies, the AHRQ methodology checklist for cross-sectional studies, and the Cochrane Risk-of-Bias tool and Jadad scale for randomized controlled trials. The protocol was registered with PROSPERO (CRD420251065070).ResultsTwenty-one studies were included after screening, of good methodological quality, involving 77,813 adolescents, including 5,259 AIS patients, published between 2015 and 2025. Physical activity was significantly associated with AIS. Most recreational sports and traditional Chinese sports may prevent AIS, while long-term participation in competitive sports, dance, and artistic gymnastics were risk factors for AIS. Adolescents need to achieve a minimum threshold of one hour of daily physical activity to effectively prevent spinal scoliosis.ConclusionAppropriate physical activity may reduce AIS risk. Schools should enhance their focus on adolescent physical activity and establish an integrated “school-family”, “school-medical”, and “school-sports” approach to support scoliosis prevention and promote healthy adolescent development.Systematic Review Registrationhttps://www.crd.york.ac.uk/, PROSPERO (CRD420251065070).